Improving Effective Communication in Students’ Classroom Presentation - Dita Surwanti (Journal of English Education, Literature and Linguistics, 2019)
This research was conducted to improve the effective communication in students’ classroom presentation. Based on the phenomena happened in classroom presentations, the researcher found that there was a tendency in doing slide reading during presentations. Thus the researcher formulated this research question: “How can effective communication be achieved in students’ classroom presentation?” Since it was a practical problem that should be solved together by the researchers and the participants, thus action research was applied to solve the problem. There were several theories used to answer the research questions; theory of communication, communication skills and speaking skills. This research was conducted using three cyclical processes. Based on the classroom observation, there were improvements in doing classroom presentations. The participants had given clear and unambiguous explanation, congruent material, accurate message, and feedback although there was still weakness in the criteria of giving specific examples.